PENGARUH PELATIHAN LARI INTERVAL DAN HOLLOW SPRINT TERHADAP KAPASITAS VITAL PARU - Dody Sutiawan, I Wayan (Jurnal Ilmu Keolahragaan Undiksha, 2013)
This research aimed to determine the effect of interval training and hollow sprint run to lung vital capacity. This research was quasi-experimental with "The Non-randomized control group pretest-posttest design". The subjects were the Â participants of extracurricular student football junior high school of Sila Candra Batubulan amounting 45 people. Lung vital capacity was measured by a spirometer. Data were analyzed by independent t-test, one way anova and further test (LSD) at the 0.05 significance level with SPSS 16.0. Based on independent t-test results of lung vital capacity variable for interval run training group and hollow sprint training group shared the significance of 0.000. one way anova test results of the two data paths from the training group significance value of 0.000 so the comparison test. Based on the test results obtained LSD mean difference of data interval run training group better than hollow sprint training group. From the results of the data analysis and discussion, it can be concluded that the interval run training and hollow sprint training effect on lung vital capacity, which interval run training is more significant effect on the increase of lung vital capacity of extracurricular football student participants junior high school of Sila Candra Batubulan academic year 2012/2013 .